Evaluating Adults With Idiopathic Pancreatitis for Genetic Predisposition. Issue 1 (January 2015) - Ballard, Darren D.; Flueckiger, Joyce R.; Fogel, Evan L.; McHenry, Lee; Lehman, Glen A.; Watkins, James L.; Sherman, Stuart; Coté, Gregory A.
<x xml:space="preserve">Abstract</x> Objectives In adults with unexplained pancreatitis, the yield of complete gene versus select exosome sequencing on mutation detection and distinguishing clinical characteristics associated with mutations requires clarification. We sought to (1) compare frequency of mutations identified using different techniques and (2) compare clinical characteristics between adults with and without mutations. Methods This is a cohort study of adults with unexplained pancreatitis who underwent genetic testing between January 2008 and December 2012. We compare probabilities of having a positive mutation with complete gene sequencing versus alternatives and describe differences in characteristics among patients with and without mutations. Results Of the 370 patients, 67 (18%) had a genetic mutation; 24 (6%) were of high risk. Mutations were significantly more prevalent with use of complete sequencing (42%) versus other approaches (8%, P < 0.0001). Most (44/67, 66%) with a mutation had no family history. Those with high-risk mutations were more likely to have a family history of chronic pancreatitis (21% vs 4%, P = 0.002). Patients with pancreas divisum were more likely to have mutations (27% vs 14%, P = 0.0007). Conclusion Among individuals with adult-onset pancreatic disease, the probability of finding any mutation, including high risk, is significantly higher using complete gene sequencing. The impact on patients and providers requires further investigation.